Changes in attitudes towards gender norms following childbirth - Lucas Van der Velde (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2022)
While the increase in the gender wage gap following childbirth is well-documented in the literature much less is known about what stands behind this development. This research focuses on one possible channel: changes in attitudes towards gender roles. Using longitudinal data from several European countries, I show that respondents tend to adopt more conservative views following childbearing, particularly in the case of the importance of having a child, and whether men should have priority when jobs are scarce. Moreover, the relation appears to be driven by respondents in countries where women shoulder a bigger share of household chores, and where less formal care is available.
Keywords: J13; J16; 330; gender norms; child-birth; cross-country comparison; institutions